The Effectiveness of Red Ginger Therapy on Reducing Pain in Rheumatoid Arthritis Patients in the Nursing Home Guna Budi Bakti Medan in 2025 - Julimanto Hia; Helen Triwati Ziraluo; Istiqomah Istiqomah; Stella Anjuliani Sihite; Surpan Manto Situmorang; Karmila Br Kaban (Jurnal Ners, 2025)
Background: Rheumatoid arthritis is a common autoimmune infectious disorder that can cause permanent joint damage. In RA disease, patients often face a number of health problems. One of the most common is pain. One of the pain treatments is nonpharmacologically with a warm compress of red ginger. The content of compounds in red ginger, namely gingerol and shogoal, has the benefit of minimizing pain because these compounds are spicy and hot and have the characteristics of non-steroidal inflammation. Purpose: to identify the pain scale in rheumatoid arthritis patients before and after the administration of red ginger therapy. To know the effectiveness of red ginger nonpharmacology therapy on pain reduction in rheumatoid arthritis patients. Method: The type of this study is quantitative, with a one group pretest-posttest design. The population in this study were all 57 elderly people suffering from rheumatoid arthritis. The research sample was selected using purposive sampling technique, namely 25 samples. Data collection used observation of the sample as well as obtained from the nursing home manager. Pain measurement using the face pain scale. Data analysis using the wilcoxon signed rank test. Results: the final result using the wilcoxon signed rank test obtained p = value 0.00 <α0.05. Conclusion: The pain scale in RA patients before and after giving red ginger therapy has a significant difference. There is an effectiveness of red ginger therapy on reducing pain in RA patients.